COROSOLIC ACID: A SYNOPSIS ON ITS ANTICANCER PROPERTIES - Chan, Eric Wei Chiang; Wong, Siu Kuin (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Corosolic acid (CA) or 2β-hydroxyursolic acid is an ursane-type pentacyclic triterpene with a molecular formula of C30H48O4 and molecular weight of 473 g/mol. The 30-carbon skeleton and five six-membered rings (A−E) of CA are structurally similar to those of ursolic acid, asiatic acid, and 23-hydroxyl CA. CA was first isolated from the leaf of Lagerstroemia speciosa and later from the fruit of Crataegus pinnatifida. Although L. speciosa (Lythraceae) remains the most important source of CA, Rosaceae and Lamiaceae are the dominant families. This synopsis is focused on the anticancer properties of CA as recent studies have generated new and additional knowledge on its oncology. CA has antitumor, antiproliferative, and apoptotic activities against many types of human cancer cells (including some murine cancer cells), which are inhibited through different molecular mechanisms. Non-apoptotic cell death has also been reported. Depending on the type of cancer cells, the cytotoxicity of CA is comparable to ursolic acid, its analog. Currently, there are no studies on the structure-activity relationship of CA. In ursolic acid, which is structurally similar to CA, the −OH group at C-3 and the −COOH group at C-28 exhibited cytotoxic activity.